Considerations on the Roman Empire and the development of Christianity - Vaz Stein, Anderson Leonardo (Romanitas - Revista de Estudos Grecolatinos, 2025)
Book review of: CHEVITARESE, A. L.; SILVA, G. V. (org.). Cristianismos no Império Romano. Rio de Janeiro: Menocchio, 2023. 344 p.
Keywords: Roman Empire; Religion; Christianity